The Preparation, Antioxidant Activity Evaluation, and Iron-Deficient Anemic Improvement of Oat (Avena sativa L.) Peptides–Ferrous Chelate - Yuanqing, He; Pengyao, Yang; Yangyang, Ding; Min, Chen; Rui, Guo; Yuqing, Duan; Haihui, Zhang; Haile, Ma (Frontiers in Nutrition, 2021)
Iron-chelating peptides have been widely considered as one of the best iron supplements to alleviate the iron deficiency. In this study, a novel oat peptides–ferrous (OP-Fe2+) chelate was prepared from antioxidant oat peptides obtained in the laboratory of the authors. The optimal preparation condition was obtained through the single-factor and response surface methodology, and the chelating rate could reach up to 62.6%. After chelation, the OP-Fe2+ chelate exhibited a significantly higher 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity than oat peptides. It was discovered that the hemoglobin concentration and the number of red blood cell levels in OP-Fe2+-treated iron-deficient anemic (IDA) rats were significantly higher than untreated IDA rats. The OP-Fe2+ chelate could also improve the hypertrophy of the spleen, serum iron (SI), total iron and binding capacity, and serum ferritin levels in the IDA rats. In addition, the OP-Fe2+ treatment significantly increased the antioxidant activities of super oxidase and glutathione in the liver homogenate of the IDA rats. Therefore, the OP-Fe2+ chelate is an effective type of iron supplement for IDA rats, which could be a promising source with anti-anemia and antioxidant activity.